2019
DOI: 10.1098/rspb.2019.1578
|View full text |Cite
|
Sign up to set email alerts
|

Climate drives spatial variation in Zika epidemics in Latin America

Abstract: Between 2015 and 2017, Zika virus spread rapidly through populations in the Americas with no prior exposure to the disease. Although climate is a known determinant of many Aedes -transmitted diseases, it is currently unclear whether climate was a major driver of the Zika epidemic and how climate might have differentially impacted outbreak intensity across locations within Latin America. Here, we estimated force of infection for Zika over time and across provinces in Latin America using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
3
15
0
Order By: Relevance
“…The spatial variation of ZIKV in Colombia indeed has been verified in the literature [37–39], while no direct evidence shows that the spatial variation of ZIKV was associated with climate change. Our findings on the best meteorological predictors are consistent with the results of a previous study, which analyzed the data in the whole Latin America [40]. In this study, the meteorological predictors can only explain 36-39% of the spatial variation of ZIKV, revealing that there are still additional non-meteorological factors which can explain the spatial variation of ZIKV.…”
Section: Discussionsupporting
confidence: 91%
“…The spatial variation of ZIKV in Colombia indeed has been verified in the literature [37–39], while no direct evidence shows that the spatial variation of ZIKV was associated with climate change. Our findings on the best meteorological predictors are consistent with the results of a previous study, which analyzed the data in the whole Latin America [40]. In this study, the meteorological predictors can only explain 36-39% of the spatial variation of ZIKV, revealing that there are still additional non-meteorological factors which can explain the spatial variation of ZIKV.…”
Section: Discussionsupporting
confidence: 91%
“…Prediction of climatic conditions in advance can help in forecasting the emergence and propagation of pathogenic viruses and bacteria or their vectors. Harris et al ( 2019 ) showed that climate conditions i.e. relative humidity, temperature, and the population are the key determinants related to the occurrence of an endemic in a particular geographical region.…”
Section: Environmental Issues and The Emergence Of Pandemicsmentioning
confidence: 99%
“…In the first equation, the cumulative distribution function of the ZIKV generation time was denoted by F ZIKV . This was estimated by Ferguson et al and subsequently used by Harris et al to obtain the weight parameters ω u 's [10,46]. In the second equation, M units.…”
Section: Susceptible Spatial Units With Cryptic Spread Of Zikvmentioning
confidence: 99%